Variability of Gravity Wave Effects on the Zonal Mean Circulation and Migrating Terdiurnal Tide as Studied With the Middle and Upper Atmosphere Model (MUAM2019) Using a Nonlinear Gravity Wave Scheme - Lilienthal, Friederike; Yiğit, Erdal; Samtleben, Nadja; Jacobi, Christoph (Frontiers in Astronomy and Space Sciences, 2020)
Implementing a nonlinear gravity wave (GW) parameterization into a mechanistic middle and upper atmosphere model, which extends to the lower thermosphere (160 km), we study the response of the atmosphere in terms of the circulation patterns, temperature distribution, and migrating terdiurnal solar tide activity to the upward propagating small-scale internal GWs originating in the lower atmosphere. We perform three test simulations for the Northern Hemisphere winter conditions in order to assess the effects of variations in the initial GW spectrum on the climatology and tidal patterns of the mesosphere and lower thermosphere. We find that the overall strength of the source level momentum flux has a relatively small impact on the zonal mean climatology. The tails of the GW source level spectrum, however, are crucial for the lower thermosphere climatology. With respect to the terdiurnal tide, we find a strong dependence of tidal amplitude on the induced GW drag, generally being larger when GW drag is increased.